Effect of confining pressure on soil-water characteristic curve and unsaturated shear strength - Tan, Jeremy (2017)
How confining pressure affects the soil-water characteristic curve (SWCC) is not well understood as most SWCC tests are conducted without confining pressure. Furthermore, SWCC fitting parameters obtained from such tests are used to estimate the unsaturated shear strength of soils through predictive equations. Hence, the equations may not give an accurate prediction for the shear strength of soil when confining pressures are applied. To obtain more accurate predictive equations, this project investigated the effect of different confining pressures on the SWCC and unsaturated shear strength of a compacted soil. When confining pressure was increased, the study found that void ratio decreased while air-entry value (AEV) and ϕb increased. The predictive equations, developed by Goh et al. (2010), also appeared to underestimate the unsaturated shear strength beyond the AEV. Hence, some modifications were proposed for the Goh et al. (2010) model for more accurate predictions of unsaturated shear strength when confining pressures are taken into account.